A Literature Review on First-Time Parents: Factors Associated with Coparenting in Infant Care and Implications for Counseling Practice - Fairuz Calista Nur Fadhila; Sri Redatin Retno Pudjiati; Santy Yanuar Pranawati (KONSELOR, 2026)
The transition to first-time parenthood is a challenging developmental period that can potentially influence the quality of the coparenting relationship. This narrative literature review examines factors that impact coparenting among parents of their first child. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines, focusing on studies published between 2020 and 2025. An initial search identified 2020 articles, of which 10 studies met the inclusion criteria for detailed analysis. The criteria for this review include peer-reviewed scientific articles that discuss factors or determinants of coparenting among new parents during the transition to parenthood. Findings from this review identified various factors associated with coparenting across three main levels: individual, family, and extrafamilial. The review found that at the individual level, factors such as parental mental health, reflective function, gender role expectations, parenting beliefs, nurturing beliefs, childhood maltreatment history, parenting and coparenting styles from the family of origin, and infant characteristics were influential. At the family level, factors such as prenatal marital conflict, positive prenatal couple behaviour, destructive conflict, conflict management skills, maternal gate-closing behaviour, daily coparenting practices, and partner task allocation were significant. Finally, at the extrafamilial level, social crises related to health and social support, as well as work and financial conditions, are shaped by sociocultural factors. Moreover, the findings highlight the importance of a holistic understanding of coparenting influences to enrich theoretical knowledge and provide a strong foundation for developing more effective, family-specific interventions.